1998
DOI: 10.1111/j.1834-7819.1998.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐extraction bleeding—An aid to diagnosis? Case report

Abstract: Haemophilia A, the most common of bleeding disorders is characterized by bruising and spontaneous bleeding into the joints but may remain undiagnosed if present in the mild form. A case is discussed where episodes of bruising and joint swelling as a child were misdiagnosed as rheumatic fever and the bleeding disorder was diagnosed following recurrent episodes of bleeding after extraction of an upper molar tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It was reported that some patients are diagnosed following oral symptoms and complications that occur during and after dental treatment [13][14][15]18]. Case reports have described submucosal hemorrhaging, gingival bleeding, petechiae, ecchymosis, and hematomas in patients with IDPF [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that some patients are diagnosed following oral symptoms and complications that occur during and after dental treatment [13][14][15]18]. Case reports have described submucosal hemorrhaging, gingival bleeding, petechiae, ecchymosis, and hematomas in patients with IDPF [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, most hemophilia patients are diagnosed preoperatively and tooth extractions are performed with a personalized hemostasis management plan. After performing a literature review, we found 2 cases of mild hemophilia after oral invasive surgery (tooth extraction [ 5 ] and electrosurgical resection of pericoronal flap [ 6 ]), while the two case reports lack preoperative APTT results. There are some patients with normal preoperative APTT results who had uncontrollable bleeding after surgeries (including tonsillectomy [ 7 ], ocular trauma [ 8 ], thyroidectomy [ 9 ]), and they were diagnosed with mild hemophilia A by factor assays eventually.…”
Section: Introductionmentioning
confidence: 99%